Diabetes Management Delivery and Pregnancy Outcomes in Women with Gestational Diabetes Mellitus during the First Wave of the 2020 COVID-19 Pandemic: A Single-Reference Center Report. (7th July 2021) - Wilk, Magdalena; Surowiec, Paulina; Matejko, Bartłomiej; Wróbel, Albert; Zięba-Parkitny, Joanna; Cyganek, Katarzyna; Huras, Hubert; Małecki, Maciej T.
Abstract : Objectives. The COVID-19 pandemic has forced a rapid adaptation of healthcare services to secure care for many patient groups. This includes women with gestational diabetes mellitus (GDM). We evaluated the impacts of the first COVID-19 wave on parameters such as the GDM treatment, glycemic control, and pregnancy outcomes. Methods. In this retrospective study from a reference diabetes center (Krakow, Poland), we compared patient data from two different time periods: the first wave of the COVID-19 pandemic (March 2020–June 2020) and the preceding five months (October 2019–February 2020). Data was collected from the medical records and telephone surveys. Results. We included 155 consecutive women (group N 1 = 73 and group N 2 = 82 from the COVID-19 pandemic period and non-COVID-19 period, respectively). During the COVID-19 pandemic, almost half of all GDM women (N 1 = 36, 49.3%) used telemedicine as a method of contacting their diabetic specialists while this tool was not utilized in the earlier period. Moreover, these patients reported difficulties in performing blood glucose self-control more often (N 1 = 20, 27.4%, vs N 2 = 7, 8.5%; p ≤ 0.01 ) and spent less time on diabetes education than the control group on average (N 1 = 39, 53.4%, vs N 2 = 9, 9.8% below 2 hours of training; p ≤ 0.01 ). Most analyzed glycemic parameters and pregnancy outcomes were similar. Differences were found with respect to the incidence of prolonged labor (N 1 = 12, 16.4%, vs N 2 = 3, 3.7%; p ≤ 0.01 ) and preeclampsia (N 1 = 0 vs N 2 = 7, 8.5%; p = 0.01 ). Conclusion. In this single-center observational study, the first wave of the COVID-19 pandemic did not seem to have a negative impact on pregnancy outcomes in GDM women, despite the difficulties in diabetes management delivery.